Numerical analysis of conjugate heat transfer in a partially open square cavity with a vertical heat source - Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2008)
Conjugate heat transfer in partially open square cavity with a vertical heat source has been numerically studied. The cavity has an opening on the top with several lengths and three different positions. The other walls of cavity were assumed adiabatic. The heat source was located on the bottom wall of cavity and it has got a width such as Printed Circuit Boards (PCB). Steady state heat transfer by laminar natural convection and conduction is studied numerically by solving two dimensional forms of governing equations with finite difference method. The results were reported for various governing parameters such as Rayleigh number (10(3) <= Ra <= 10(6)), conductivity ratio, opening position, opening length, PCB distance and PCB height. The numerical results were discussed with streamlines, isotherms, Nusselt number and velocity profiles on x- and y-directions. It is found that ventilation position has a significant effect on heat transfer. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Conjugate heat transfer; Electronic cooling; Partially open cavity